Sosyal medyada mahremiyet algısının çöküşü: ınstagram örneği - Sepetci, Nurten (My University, 2017)
Enformasyon teknolojilerinin gelişmesi iletişim biçimlerimizde ve günlük yaşamımızda pek çok şeyi değiştirmiştir. Özellikle internetin ortaya çıkması ve yaygınlaşmasıyla kullanıcıların bilgi ve içerik paylaşım şekilleri her geçen gün değişmektedir. Sanal ortamdaki bu yeni sosyalleşme biçimlerinin merkezinde ise sosyal paylaşım siteleri bulunmaktadır.Sosyal medyanın çok kısa bir süre içerisinde bireysel ve toplumsal hayatımızın içine bu kadar yerleşmesi, bu çalışmanın ortaya çıkma sebeplerinden biridir. Yeni bir medya olarak görebileceğimiz sosyal medyada, yaşanılan her anın paylaşılması gerektiğine dair bir kültür oluşmuş, özellikle gençlerde yaşadıkları ve düşündükleri her şeyi takipçileriyle paylaşma isteği artmıştır. Kullanıcılar, takipçileri tarafından beğenilme, onaylanma ve takdir edilme arzusunu tatmin etmek için özel yaşamlarına ait birçok bilgi ve içeriği paylaşmaktadır. Çünkü yapılan paylaşımların birçoğu mahrem olarak görülmemekte, paylaşım yapmanın sosyalleşmenin bir parçası olduğu savunulmaktadır.Çalışmada çoğunluğunu üniversite öğrencilerinin oluşturduğu 200 kişiye sosyal medya ve Instagram kullanımlarını araştıran anket yöntemi uygulanmıştır. Elde edilen sonuçlara göre, katılımcıların çoğu kişisel bilgilerini ve özel yaşamına ait fotoğraflarını paylaşmaktan rahatsız olmamakta, bunların paylaşılmasının mahremiyetlerini ihlal etmediğini düşünmektedir. Ayrıca kullanıcıların büyük bir kısmı sosyal medyanın güvensiz ve tehlikeli olduğunu düşünmekte, buna rağmen paylaşım yapmayı sürdürmektedir.Bu çalışmada genel olarak sosyal paylaşım sitelerinin toplumsal hayata etkileri, insanların sosyal medyadaki mahremiyet algıları ve paylaşma isteğinin sosyal ve psikolojik tarafları ele alınmaktadır.

The development of information technologies has led to change lots of things in the methods of communication and daily life activities in the last decades. The emergence of internet and its proliferation, specifically, has affected the attitudes of internet users towards the ways of information sharing in their daily lives. In this regard, it is possible to state that the social networking websites are the centre of new instruments of socialisation in virtual platform.The reason why this study is important that social media has managed to be an indispensable part of individual and communal lives in a short time. The idea, which is the necessity of sharing everything on social media like a new cultural behaviour, are generally accepted by internet users. The desire of sharing everything from their daily life activities to their thoughts on the current issues, therefore, has increased among internet users, particularly teenagers.The users of social media have shared everything from their private life on the social platforms in order to satisfy their desires through having an attraction for their followers, being hailed, and recognising by their followers. In this sense, they don’t think that the sharing of everything on social media is not a treat to privacy. The social media users, moreover, claim that sharing of everything on social media is one of the most important part of socialisation in nowadays.In this study, questionnaire survey is used in order to analyse the attitudes of 200 persons, mostly university students, on social media and Instagram. According to results, the most of the participants don’t have any problem to share their personal information and photos from their private lives on social media and Instagram. The results also show that the sharing of personal information on social media and in particular to Instagram is not associated with invasion of privacy by participants. They, however, persist to share their photos and private information on social media although the participants remark that social media is insecure and hazardous.In general, this study discusses on the impact of social networking websites on the human life; the privacy perception of people on social media; and social and psychological aspects of the sharing ambitious.
Keywords: Ahlaksal yönler; İletişim; Sosyal medya; sosyal medyamahremiyetinstagram social mediaprivacyinstagram; Sosyal yönler; Teknoloji